The Effects of Financial Literacy, Risk Perception, And Self-Control on Interest in Using The Shopee Paylater Fintech Service (A Study of Gen Z in Denpasar) - Anak Agung Istri Meinda Kartika; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
The growth of financial technology (fintech) in Indonesia, particularly in the Industry 4.0 era, has accelerated significantly. This development is driven by digital transformation and high levels of technology adoption, especially among the younger generation. A survey by Kredivo and the Katadata Insight Center (KIC) indicates that domestic PayLater users are predominantly millennials and Gen Z. Although PayLater users are dominated by millennials and Gen Z, when compared in terms of financial literacy, the data shows that Gen Z has the lowest financial literacy. Furthermore, while the use of fintech services like Shopee PayLater provides easier access to shopping, its use also carries potential risks. Additionally, aside from being influenced by financial literacy and risk perception, interest in using Shopee PayLater can also be influenced by self-control. The objective of this study is to test and determine the influence of financial literacy, risk perception, and self-control on interest in using the Shopee PayLater fintech service. This study was conducted in the city of Denpasar. The population in this study consists of Generation Z in Denpasar, totaling 226,450 people in 2024. The sample size was determined using the Slovin formula; based on the calculation using the Slovin formula, the sample size for this study was set at 100 respondents. Furthermore, the technique used for sample selection was purposive sampling. Data collection methods included observation, interviews, and questionnaires. The data analysis technique used was multiple linear regression. The results of the study indicate that financial literacy has a positive and significant effect on interest in using Shopee Paylater fintech among Generation Z in Denpasar; risk perception has a positive and significant effect on interest in using Shopee Paylater fintech among Generation Z in Denpasar; and self-control has a positive and significant effect on interest in using Shopee Paylater fintech among Generation Z in Denpasar.